ANALISIS STRATEGI PENGEMBANGAN PERIKANAN RAJUNGAN DI PANTAI PUDING BANGKA SELATAN - Dewi Rachma dini; Kurniawan Salim; Arief Febrianto (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2020)
The swimming crab is a type of sea crab whose abudance is distributed almost evenly across Indonesian waters. There are aspect that need to be considered in the use of swimming crab resources, namely biological technical, and economical aspect. So, taht it can be done without endangering the sustainability of the resources. The research was conducted from April through July, 2018, in Puding Beach, South Bangka Regency. The primary and secondary data were obtained using 3 method of analysis, namely analysis of maximum sustainable yield (MSY), analysis of utilization rates, business analysis, and SWOT analysis. The result suggested that the MSY value was of 1,319.059 ton/year and the foptimum was 23,877.356 trips/year. This suggests that overfishing has taken place ang that the utilization of swimming crab resources has surpassed the limit of TAC. the fishing gear used by fisherman for catching swimming carbs in Puding Beach is the collapsible trap with the operating principle of one day fishing. Based on business analysis, it was found that the activity is profitable for the fisherman and tah business if feasible. The researchers also formulated 12 alternative strategies for crab meat business development in Puding Beach.